RESTORATIVE JUSTICE DALAM TINDAK PIDANA MEREK (ANALISIS TEORI PENEGAKAN HUKUM) - Pinem, Rocky FJ; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This article analyzes the application of the concept of Restorative Justice in the context of trademark offenses and outlines how this approach can strengthen the framework of law enforcement. In the era of globalization, the serious threat of trademark offenses to business and innovation has increased, demanding an inclusive approach to address this issue. This paper discusses how the police can integrate the principles of Restorative Justice, including a holistic understanding of cases, mediation between offenders and victims, the role of the community in recovery, supervision and follow-up, as well as prevention education and public awareness. Considering the important role of the police in preventing trademark offenses, this research highlights the importance of collaboration between the police, government agencies, and the community in effectively enforcing the Restorative Justice approach. This paper also highlights the need for continuous evaluation and improvement as well as the involvement of technology in implementing Restorative Justice. Through this approach, it is hoped that the justice system can become more inclusive and sustainable, creating an environment that respects innovation and creativity in society.Keywords: Restorative justice, trademark offenses, law enforcement